Pathogenesis and Transmission Assessments of Two H7N8 Influenza A Viruses Recently Isolated from Turkey Farms in Indiana Using Mouse and Ferret Models - Sun, Xiangjie (J Virol, 2016)
Avian influenza A H7 viruses have caused multiple outbreaks in domestic poultry throughout North America, resulting in occasional infections of humans in close contact with affected birds. In early 2016, the presence of H7N8 highly pathogenic avian influenza (HPAI) viruses and closely related H7N8 low-pathogenic avian influenza (LPAI) viruses was confirmed in commercial turkey farms in Indiana. These H7N8 viruses represent the first isolation of this subtype in domestic poultry in North America, and their virulence in mammalian hosts and the potential risk for human infection are largely unknown. In this study, we assessed the ability of H7N8 HPAI and LPAI viruses to replicate in vitro in human airway cells and in vivo in mouse and ferret models. Both H7N8 viruses replicated efficiently in vitro and in vivo, but they exhibited substantial differences in disease severity in mammals. In mice, while the H7N8 LPAI virus largely remained avirulent, the H7N8 HPAI virus exhibited greater infectivity, virulence, and lethality. Both H7N8 viruses replicated similarly in ferrets, but only the H7N8 HPAI virus caused moderate weight loss, lethargy, and mortality. The H7N8 LPAI virus displayed limited transmissibility in ferrets placed in direct contact with an inoculated animal, while no transmission of H7N8 HPAI virus was detected. Our results indicate that the H7N8 avian influenza viruses from Indiana are able to replicate in mammals and cause severe disease but with limited transmission. The recent appearance of H7N8 viruses in domestic poultry highlights the need for continued influenza surveillance in wild birds and close monitoring of the potential risk to human health. IMPORTANCE H7 influenza viruses circulate in wild birds in the United States, but when the virus emerges in domestic poultry populations, the frequency of human exposure and the potential for human infections increases. An H7N8 highly pathogenic avian influenza (HPAI) virus and an H7N8 low-pathogenic avian influenza (LPAI) virus were recently isolated from commercial turkey farms in Indiana. To determine the risk that these influenza viruses pose to humans, we assessed their pathogenesis and transmission in vitro and in mammalian models. We found that the H7N8 HPAI virus exhibited enhanced virulence, and although transmission was only observed with the H7N8 LPAI virus, the ability of this H7 virus to transmit in a mammalian host and quickly evolve to a more virulent strain is cause for concern. Our findings offer important insight into the potential for emerging H7 avian influenza viruses to acquire the ability to cause disease and transmit among mammals.